USERS’ ENGAGEMENT IN BANKING ACTIVITIES ON SOCIAL MEDIA: A STUDY WITH REFERENCE TO FACEBOOK - Mani, R.; Thiyagarajan, S.; Azhaguraja, N.; Janakiraman, S. (Copernican Journal of Finance & Accounting, 2022)
This study was conducted to assess the users’ (customers’) engagement in Indian commercial banks on social media through customer reactions (likes, comments and shares) to the banking activities (banks’ Facebook page posts) on Facebook. The data was collected through Facebook for a period of five and half years (June 2016 to December 2021). This paper also found the presence of Indian commercial banks on various social media platforms. The results show that most of the commercial banks are present in popular social media platforms and all the banks are present on Facebook as well. With respect to users’ engagement in social media, private sector banks have more engaged users, especially in ICICI bank in comparison to public sector banks even though there are more public sector banks’ activities.